99 SPEEDMART Sdn Bhd / Mohd Jawahir Ahmad Aramli, Ahmad Fuad Omar and Muhammad Heedir Shamsulkamar - Ahmad Aramli, Mohd Jawahir; Omar, Ahmad Fuad; Shamsulkamar, Muhammad Heedir (2017)
This study focuses on in-depth of a grocery store establishment which is considered to be common type of business with tons of competition anywhere all over the nation. The neat, advance and systematic management with excellent logistic system should be highlight and to look deep into. 99 Speedmart is a grocery market business in Malaysia originated from Klang Selangor. It Focuses on concept-oriented mini market with over than 3500 types of daily use products. They were able to achieve optimum economies of scale via bulk purchases of goods by leveraging on a large chain supported by fully-intergrated distribution centres working in synergy with an advance logistic system, thereby achieving increased efficiency and reduced costs. SPEEDMART portrays a fast, easy & convenient store that focuses on quality and speedy customer service. 99 Speedmart has from a single grocery store in 1987 grown to open more than 1000 branches as for September 2017.